Study on the Material Properties of Cement-sand-gravel. Issue 1 (June 2020) - Li, Xiuwen; Zhang, Shunfu; Wu, Hao; Tian, Dongcheng
Abstract: Cement-sand-gravel dam is a new type of dam. The low-strength cement-sand-gravel material with low price is used for dam construction. This material is obtained by simply mixing water with a small amount of cement in the sand gravel of river bed or excavation waste slag and other materials easy to get near the dam site. In this paper, the effects of water binder ratio, fly ash, sand ratio, stone powder and other parameters in different mix ratio design on the properties of materials are studied. The results show that: (1) water to binder ratio has a great influence on the strength of cement-sand-gravel material; (2) fly ash can increase the later strength of cement-sand-gravel material; (3) when the sand ratio exceeds 25%, with the increase of sand ratio, the compressive strength of cement-sand-gravel material decreases sharply; (4) stone powder has a significant effect on the early strength.